The devil is a part-timer! 14 - Wagahara, Satoshi (Yen Press, 2019)
"The renovations at MgRonald are finally complete, so it's back to work for Maou! Meanwhile, Chiho looks back on her experiences at Tokyo Tower and resolves to get stronger. But when a new demon and a certain boy show up, Chiho, Emi, and Maou will have to prove their strength in more ways than one!"--Page [4] of cover.